Terahertz phenomena in the strong coupling regime - Kristinsson, Kristinn (2017)
Emission and utilization of terahertz range electromagnetic radiation is an active area of research. This thesis is divided into two main parts, in the first of which a scheme of generation of THz radiation from the dipolariton system is presented. Dipolarions, a form of exciton-polaritons, are hybrid light-matter particles, arising in a semiconductor microcavity with embedded double quantum wells from the strong coupling between the confined photon and spatially direct and indirect excitons. Oscillations between the direct and indirect excitons and associated oscillation in dipole moment is shown to couple to an external THz cavity mode, resulting in coherent THz emission.